Achieving cup target as per spinopelvic assessment is associated with improved THA outcome: a prospective, multicentre study - Verhaegen, Jeroen; Innmann, Moritz Maximilian; Vorimore, Camille; Merle, Christian; Grammatopoulos, George (HIP international, 2025)
Background: Different methods can help to optimise sagittal cup orientation in total hip arthroplasty (THA) based on individual spinopelvic characteristics. This study aimed to: (1) assess how often combined sagittal index (CSI) and hip-spine-classification targets were achieved post THA; (2) compare anteversion/inclination between cups in-/outside optimal CSI zone; and (3) determine association with outcome. - Methods: This is a multicentre, prospective, case-cohort study of 435 primary THA for osteoarthritis (53% females; age: 65 ± 12 years; follow-up: 2.4 ± 0.6 years) (58% lateral, 29% anterior, 13% posterior approach). No robotics or dual-mobility were used. Patients underwent spinopelvic radiographs to measure parameters including lumbar lordosis (LL), sacral slope (SS), pelvic tilt (PT), pelvic incidence (PI), pelvic femoral angle (PFA), and ante-inclination (AI) on lateral spinopelvic radiographs. Unbalanced spine was defined as PI - LL ⩾ 10° (PI: pelvic incidence; LL: lumbar lordosis), stiffness as ∆LL < 20°. Optimal cup orientation was based on CSI targets: 205-245° for balanced spine (n = 327), or 215-235° for unbalanced spine (n = 108), hip-spine classification targets (±5°), and conventional inclination/anteversion (40/20° ± 10°) target. Patient-reported outcome was measured using Oxford Hip Score (OHS). - Results: CSI targets were achieved in 60% (n = 261/435), whilst 44% had cup position within hip-spine classification targets (n = 125/284). Anteversion was higher among cups within CSI targets (26° ± 8° vs. 22° ± 10°; p < 0.001). Overall dislocation rate was 0.9% (n = 4/435), without difference whether CSI targets were achieved (0.4% vs. 1.7%; p = 0.178). Postoperative OHS was better among those within CSI targets (42 ± 8 vs. 40 ± 9; p = 0.003) or within hip-spine-classification targets (p = 0.028), but not according to conventional orientation (p = 0.384). - Conclusions: Awareness of adverse spinopelvic characteristics and using sagittal characteristics (especially CSI) can help surgeons to achieve optimal cup orientation, improving outcome and reducing dislocation risk post-THA.
Gesehen am 22.09.2025